Bandgap variation in size controlled nanostructured Li-Ni co-doped CdO thin films - Gupta, R. K.; Serbetci, Z.; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2012)
Li and Li-Ni doped CdO thin films were fabricated using sol-gel spin coating technique. Surface property and particle size of the pure CdO and doped CdO films were investigated using atomic force microscopy. The particle size of the films is of nanometer size and it changes with the doping concentrations. The optical study revealed that the bandgap of the films decreases with Li doping level. On the other hand for Li-Ni co-doped films, the bandgap first decreases with increase in Li-Ni concentrations and then increases with further increase in Li-Ni doping concentrations. The observed results are explained on the basis of quantum size effect. The obtained results indicate that the nanostructure and optical bandgap of the CdO film can be controlled by Li and Ni-Li co-dopants. (C) 2011 Elsevier B. V. All rights reserved.
Keywords: CdO; Lithium; Nickel; Bandgap; Quantum confinement